Antibacterial Activity of Endophytic Fungi Isolated from Bidara Roots (Ziziphus mauritiana Lam.) Against Bacteria That Cause Skin Infections Using TLC-Bioutography - Sari, Andini Indah Permata; Fitriana, Fitriana; Amirah, Sitti (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
One common disease found in tropical countries is skin infection. Inappropriate use of antibiotics to treat skin infections can lead to bacterial resistance, making it necessary to explore the source of bioactive compounds in natural materials. The Bidara plant (Ziziphus mauritiana Lam.) is known to have antibacterial properties. This research aimed to determine the antibacterial activity of endophytic fungal isolated from the parts of the Bidara plant against bacteria that cause skin infections using the TLC-Bioautography method. In this research, the isolate with the code IFAZ-6 was purified to obtain a pure endophytic fungal isolate, and macroscopic and microscopic examinations were conducted on that isolate. The obtained isolate was fermented for 21 days at room temperature using MYB (Maltose Yeast Broth) medium. The fermentation products were extracted using ethyl acetate (1:1). The obtained extract was further tested using TLC with a chloroform: methanol eluent (7:1). The TLC-Bioautography results showed Rf values of 0.81 and 0.58 indicating antibacterial activity against Staphylococcus aureus, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Propionibacterium acnes bacteria. The identification of chemical components in the endophytic fungal isolate from the Bidara plant confirmed the presence of flavonoids, alkaloids, and anthraquinones. The extract from the endophytic fungal isolate with the code IFAZ-6 indicated antibacterial activity.